The impact of psychological well-being, employability and work-life balance on organizational mobility of women engineering technology graduate - Osman Kadir; Mohd Zaidi Omar; Mohamad Sattar Rasul (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Government has always emphasised on science, technology, engineering, and mathematics (STEM) education to meet the needs of the country's human resources in STEM fields. However, the quantity of human resources in STEM fields is quite alarming due to the deterioration in the number of students taking STEM subjects and career mobility among STEM graduates to non-STEM careers, especially female STEM graduates. Career mobility often occurs among these engineering women which has resulted in the loss of valuable human resources to the organization. Product designs produced in previous organizations will be taken to a new organization and cause the issue of product design confidentiality. This study was conducted to examine the relationship between work-life balance, employability, and psychological well-being towards inter-organizational mobility among 114 women's engineering technology graduates who are in the industry in Malaysia. A model has been developed and tested using SEM techniques using SmartPLS software. The findings show that there is a negative relationship between psychological well-being, employability, and work-life balance towards inter-organizational mobility. The findings in this study are the influence of psychological well-being plays a major role in inter-organizational mobility among women technologists. In addition, low employability also contributes to the mobility of organizations among female engineering technology graduates in the industry.